El sujeto en la práctica odontológica (práctica odontológica o práctica dental) - Nelson Cortés-C (Universidad de Antioquia, 2003)
The notion of Subject is of recent inclusion in the dental literature. Although the terms: individual, person and subject are used daily as synonymous, it is the purpose of this paper reveal its real significance; also the terms Body and Organism will be discussed because the medical profession uses as equivalents. I will intent to construct a conceptual framework in order to clarify if the dentist does or does not include the Subject in his/ her dental practice.